Discussions on the 19th Century Sokoto Jihad and Its Impact on the Down Fall of Habe Rulers in Daura-1806-1906 (LAPAI JOURNAL OF NIGERIA HISTORY, 2021)
This work among other things examines the pre-Jihad Daura traditional affairs. It highlights the origin and development of the town of Daura and how it led to the establishment of Hausa states. It also explains the emergence of Abduddar and the killing of sarki (snake) that prohibited people from getting water in the well except on Fridays, by Bayajidda and the marriage between him and the queen Daurama. This paper also highlights on traditional Habe rulers of Daura (HAUSA) that ruled for 99 years before the Jihad of Usman Danfodio. This work also enumerates the structure of Fulani system of Administration in Daura, explains how Socioeconomic and political activities were changed after the Jihad. The issue of excessive tax, confiscation of Fulani properties and other forms of oppressions done by the Habe rulers were suppressed during the Fulani reign in Daura. The paper also examines the nine Fulani rulers so far and their pattern of administration that lasted for one hundred years after which the power restored back to Hausa (HABE) ruling class by the British colonial Masters in 1906. The paper also highlights on the emergence ofthree different Daura kings at the same time in different places. That is, Sarkin Daura at Daura, Sarkin Daura at Zango (present Zango Daura) and Sarkin Daura at Baure. The paper also examines the establishment of Malam Musa Sarkin Daura-Zango as the new Sarkin Daura and the unification of Daura, Daura-Zango, and Daura-Baure under one Sarki by the British colonial masters in 1906.